Identification and quantification of redox and pH buffering processes in a heterogeneous, low carbonate aquifer during managed aquifer recharge. Issue 5 (26th May 2016) - Seibert, Simone; Atteia, Olivier; Ursula Salmon, S.; Siade, Adam; Douglas, Grant; Prommer, Henning
Abstract: Managed aquifer recharge of aerobic water into deep aquifers often induces the oxidation of pyrite, which can lead to groundwater acidification and metal mobilization. As circumneutral pH is often maintained by the dissolution of sedimentary calcite or high injectant alkalinity little attention is generally paid to potential alternative pH buffering processes. In contrast, this study analyzed water quality evolution from a 2 year long groundwater replenishment trial in an anaerobic, mostly carbonate free aquifer. While injection of aerobic, very low salinity water triggered pyrite oxidation, the comprehensive field data showed that in many aquifer zones pH was buffered without substantial release of inorganic carbon. A numerical analysis was performed to test and evaluate different conceptual models and suggested that either proton buffering or the dissolution of aluminosilicates, or a combination thereof, can explain the observed, rapid buffering at locations where carbonates were absent. In contrast to many previous managed aquifer recharge [MAR) studies, the oxidation of sedimentary pyrite by nitrate was found to be of minor importance or negligible. The study also highlights that the depositional history of the aquifer, and the associated differences in mineralogy and geochemistry, need to be considered when estimating groundwater quality evolution during the injection of various water types for aquifer replenishment or other management purposes. Key Points: Reactive processes during groundwater replenishment were studied Reactive transport modeling was used to analyze the field data Multiple conceptual/numerical models of pH buffering processes were tested against observed data